The intellectual foundations of Alfred Marshall's economic science: A rounded globe of knowledge - Cook, Simon J (Cambridge University, 2013)
This work provides a contextual study of the development of Alfred Marshall's thinking during the early years of his apprenticeship in the Cambridge moral sciences. Marshall's thought is situated in a crisis of academic liberal thinking that occurred in the late 1860s.